Cost-Utility Analysis of Add-on Cannabidiol vs Usual Care Alone for the Treatment of Seizures in Patients With Treatment-Resistant Lennox-Gastaut Syndrome or Dravet Syndrome in the Netherlands - Jamshaed Siddiqui; Sally Bowditch (Journal of Health Economics and Outcomes Research)
# Background Lennox-Gastaut syndrome (LGS) and Dravet syndrome (DS) are severe, treatment-refractory, epileptic encephalopathies that often develop in infancy or early childhood. Since December 1, 2022, plant-derived highly purified cannabidiol (CBD) medicine (Epidyolex®; 100 mg/mL oral solution) has been reimbursed in the Netherlands for the adjunctive treatment of seizures associated with LGS or DS.